Force Control of Hydraulic Actuator Based on Incremental Nonlinear Dynamic Inversion - Lian, Hongzhen; Cao, Hongli (Journal of Applied Nonlinear Dynamics, 2026)
The nonlinear dynamics of hydraulic actuators, coupled with their inherent model uncertainty, present considerable challenges in achieving accurate motion control in hydraulically driven systems. This research proposes a sampling-based incremental nonlinear dynamic inverse control methodology designed to address the force tracking problem associated with hydraulic actuators. The proposed control strategy employs differential pressure derivatives as feedback and functions independently of a precise mathematical model of the hydraulic actuator or the necessity for parameter calibration, thereby demonstrating robust resilience to model uncertainty. A theoretical analysis is performed to evaluate the robustness of the incremental nonlinear dynamic inverse control approach in the presence of parameter uncertainty, and stability bounds critical to maintaining control performance are established. The validity of the proposed method is substantiated through comparative simulations with a primary focus on the force tracking aspect.